(untitled) (Colloquia Comparativa Litterarum, 2025)
The article presents the results of a study examining the presence of comparative literature courses within the context of contemporary academic philological education. The conclusions have been drawn after examining the curricula and programmes of more than 70 universities (mainly European and North American, but also a few South American and Asian establishments of academic education). The basic models of teaching comparative disciplines have been singled out and classified based on the content of the reviewed academic courses. Their scope, status, and functions have been analysed in view of their presence in various philological and humanitarian specialties, as well as in the different stages of academic education (undergraduate and graduate).